Comparison between anterior segmental osteotomy versus conventional orthodontic treatment in root resorption: a radiographic study using cone-beam computed tomography - Bo-Yeon Hwang; Byung-Joon Choi; Baek-Soo Lee; Yong-Dae Kwon; Jung-Woo Lee; Junho Jung; Joo-Young Ohe (SpringerOpen, 2017)
Abstract Background Patients who received orthodontic treatment are likely to have apical root shortening. It appears that external apical root resorption results from a combination of patient-related risk factors such as genetic influences, systemic factors, and orthodontic treatment-related factors. Regarding the fact that the anterior segmental osteotomy (ASO) has been known for its possibility of complementing external apical root resorption and of buffering periodontal problems, it has been the preferred treatment. However, the studies on the efficacy of ASO in preserving the root are not sufficient. In this study, we compared the amount of root resorption between the patients who only received orthodontic treatment and the patients who received orthodontic treatment with ASO. Methods This study included 28 patients (the number of incisor = 198) who received orthodontic treatment with or without ASO. We categorize them into groups A and B by the type of orthodontic treatment (group A: conventional orthodontic treatment; group B: orthodontic treatment with ASO). Cone-beam computed tomographic and cephalometric evaluations were retrospectively performed on the radiographs taken for the diagnosis of the treatment before treatment and at the end of active treatment. Results In group B, root resorption itself and its rate both turned out to have significantly lower than those in group A. Also, the change of incisal angle is significantly smaller in group B than in group A. On the other hand, in group A, the change of incisal angle was positively correlated with the change of AP (anteroposterior) position. In group B, the change of incisal angle was negatively correlated with the duration of the orthodontic treatment. In group B, amount of root resorption (mm) was positively correlated with the duration of the orthodontic treatment. Conclusions The results show lesser root resorption and shorter treatment duration with ASO than with conventional orthodontic treatment. Therefore, if the indications are accurately determined, ASO can be an effective treatment option when the amount of root resorption is expected to be high, especially in late adults.